(untitled) (Journal of the Bangladesh Agricultural University, 2013)
The study examined the consumer preference for processed milk in Mymensingh town. The study was mainly based on primary data in which 40 consumers were purposively selected from Mymensingh town. In the study, preference of consumers for processed milk i.e. powder milk, condensed milk and pasteurized milk were investigated. Consumers preference for processed milk was ascertained through a 4-point numerical rating scale. The consumers highly preferred powder milk and the computed preference index of powder milk was 80. The computed preference index of pasteurized milk was 71. The computed preference index of raw milk was 54. The lowest preference of consumers was for condensed milk and the computed preference index of condensed milk was 36. The study revealed that Milk Vita has ranked first (90) followed by Diploma (85), Dano (81), Arong (68) and Red Cow (61) were the major brands preferred by the consumers. On the other hand, Danish (36), Nido (34), Starship (34), Marks (27) and Farmland (26) were less preferred for consumption of processed milk. The relationship between the factors that influencing consumers preferences and their preferences of processed milk was also explored. Spearman rank correlation coefficient test was used to explore relationship between the variables. The monthly income of the family, price level, taste level, fat content, nutritional value and attitudes towards processed milk of the consumers were significantly related with their preferences of processed milk while the other factors (age, family size, education level) were not significantly related. DOI: http://dx.doi.org/10.3329/jbau.v10i2.14918 J. Bangladesh Agril. Univ. 10(2): 267-276, 2012